The Timing and Probability of Switching to Second-line Regimen - An application to Second-Line Antiretroviral Therapy in India. - de Mello-Sampayo, F. (Munich Personal RePEc Archive, 2014)
Health fluctuations render the outcome of any treatment switch uncertain, so that decision makers might have to wait for more information before optimally switching treatments. This paper sets up a stochastic model that provides an optimal rule for the timing of treatment switch. The results of the model were then tested empirically with patient-based data on first-line and second-line antiretroviral treatment in India. The empirical results support the findings of the analytical model.